Characterization of a Novel Bat Adenovirus Isolated from Straw-Colored Fruit Bat (Eidolon helvum) - Ogawa, Hirohito; Kajihara, Masahiro; Nao, Naganori; Shigeno, Asako; Fujikura, Daisuke; Hang’ombe, Bernard; Mweene, Aaron; Mutemwa, Alisheke; Squarre, David; Yamada, Masao; Higashi, Hideaki; Sawa, Hirofumi; et al. (Viruses, 2017)
Bats are important reservoirs for emerging zoonotic viruses. For extensive surveys of potential pathogens in straw-colored fruit bats (Eidolon helvum) in Zambia, a total of 107 spleen samples of E. helvum in 2006 were inoculated onto Vero E6 cells. The cell culture inoculated with one of the samples (ZFB06-106) exhibited remarkable cytopathic changes. Based on the ultrastructural property in negative staining and cross-reactivity in immunofluorescence assays, the virus was suspected to be an adenovirus, and tentatively named E. helvum adenovirus 06-106 (EhAdV 06-106). Analysis of the full-length genome of 30,134 bp, determined by next-generation sequencing, showed the presence of 28 open reading frames. Phylogenetic analyses confirmed that EhAdV 06-106 represented a novel bat adenovirus species in the genus Mastadenovirus. The virus shared similar characteristics of low G + C contents with recently isolated members of species Bat mastadenoviruses E, F and G, from which EhAdV 06-106 diverged by more than 15% based on the distance matrix analysis of DNA polymerase amino acid sequences. According to the taxonomic criteria, we propose the tentative new species name “Bat mastadenovirus H”. Because EhAdV 06-106 exhibited a wide in vitro cell tropism, the virus might have a potential risk as an emerging virus through cross-species transmission.